A novel super high back pressure cascade heating scheme with multiple large-scale turbine units. (15th June 2020) - Ma, Liqun; Ge, Zhihua; Zhang, Fuxiang; Wei, Huimin
Abstract: The recovery of waste heat from power generation by the utilization of energy cascade for district heating has become an important method to improve the energy saving of combined heat and power (CHP) plants. In this paper, a novel super high back pressure (SHBP) cascade heating scheme is proposed to recover waste heat further and tap the energy saving potential of multi-unit combined heating system. On this basis, the regulation progress under full heating conditions is simulated. It's concluded that the regulation progress can be divide into 4 stages, and the flow of extraction steam or the back pressure of turbines is adjusted to satisfy the varying heating demand. Furthermore, the detailed thermodynamic analysis of the novel cascade heating scheme is performed. The results indicate that, in the design condition, the heating process exergy efficiency of the SHBP scheme is improved by 10.4%, leading to an addition of 136.6 MW in generating power and a decline of 30.1% in the heating consumption rate. During the whole heating period, exhaust steam heat load ratio of the SHBP system reaches to 92.5%, which brings about the average heating consumption rate only 5.30 kg/GJ, and 72 thousand tons standard coal saved in total. Highlights: A novel heating scheme with multiple units is proposed to further recover waste heat. The regulation progress under full operating conditions is simulated. The cascade heating process of thermal network is analyzed in detail. The study of energy consumption is conducted with the method of consumption rate.